Investigatons of the potential of crystalline excipients to prevent the process-induced amorphisation of active pharmaceutical ingredients - Curtin, Vincent (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2014)
The focus of this thesis was to evaluate the impact of mechanical activation (milling and dry mixing) and spray drying on the crystallinity of selected active pharmaceutical ingredients (APIs) and to explore the feasibility of co-processing these drugs with low glass transition temperature (Tg) excipients as a strategy for preventing process induced amorphisation. Co-milling investigations were initially performed on sulfadimidine and salbutamol sulphate. Based on the data obtained for these two APIs, further analysis was conducted on budesonide to see if results could be generalised to other compounds. Co-spray drying experiments were performed with sulfadimidine as API. The excipients chosen were dicarboxylic acids (glutaric, adipic, succinic, pimelic and malic acid) and sugar alcohols (mannitol and xylitol).
Keywords: Pharmacy & Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin